2017
DOI: 10.1186/s12916-017-0855-z
|View full text |Cite
|
Sign up to set email alerts
|

Disease management in the treatment of patients with chronic heart failure who have universal access to health care: a randomized controlled trial

Abstract: BackgroundThe efficacy of disease management programs in improving the outcome of heart failure patients remains uncertain and may vary across health systems. This study explores whether a countrywide disease management program is superior to usual care in reducing adverse health outcomes and improving well-being among community-dwelling adult patients with moderate-to-severe chronic heart failure who have universal access to advanced health-care services and technologies.MethodsIn this multicenter open-label … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
78
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 51 publications
(83 citation statements)
references
References 26 publications
0
78
0
3
Order By: Relevance
“…reported separate HFpEF statistics (HFpEF defined as those with EF > 45%) and found no difference in percentage with HFpEF by survived or died. Nine studies reported no significant difference of their respective interventions on mortality between either intervention groups or intervention and usual care . Kalter‐Leibovici and colleagues dichotomized findings by HF group and found no significant difference by composite outcome (all‐cause mortality/HF hospitalization), or all‐cause mortality alone, and much wider confidence intervals in those with EF ≥ 50%.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…reported separate HFpEF statistics (HFpEF defined as those with EF > 45%) and found no difference in percentage with HFpEF by survived or died. Nine studies reported no significant difference of their respective interventions on mortality between either intervention groups or intervention and usual care . Kalter‐Leibovici and colleagues dichotomized findings by HF group and found no significant difference by composite outcome (all‐cause mortality/HF hospitalization), or all‐cause mortality alone, and much wider confidence intervals in those with EF ≥ 50%.…”
Section: Resultsmentioning
confidence: 99%
“…If we use the ESC criterion that HFpEF includes an EF ≥ 50%, then seven studies are of interest. The outcomes of mortality and/or hospitalization were measured in six studies . Of these, only one had significantly fewer events in the intervention group, specifically in all‐cause mortality .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations